2013
DOI: 10.1515/cclm-2012-0521
|View full text |Cite
|
Sign up to set email alerts
|

Serum DNase I activity in systemic lupus erythematosus: correlation with immunoserological markers, the disease activity and organ involvement

Abstract: Monitoring of DNase I activity simultaneously with SLEDAI-2K might be a useful tool in the follow-up of SLE. An increase of DNase I activity characterized relapse in most SLE patients, although it did not reach the levels of healthy individuals. A decrease of DNase I activity in SLE flare-ups might be a functional biomarker of a subset of patients with specific dysfunction of apoptotic chromatin degradation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 16 publications
6
37
1
Order By: Relevance
“…Impaired degradation of chromatin by DNase1 in the process of clearance of apoptotic material is supposed to contribute to the development of SLE. In accordance with this it was shown that DNase1 activity is lower in SLE patients than in healthy individuals [39,40]. Here, we investigated DNase1 activity in the course of SLE disease progression.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Impaired degradation of chromatin by DNase1 in the process of clearance of apoptotic material is supposed to contribute to the development of SLE. In accordance with this it was shown that DNase1 activity is lower in SLE patients than in healthy individuals [39,40]. Here, we investigated DNase1 activity in the course of SLE disease progression.…”
Section: Discussionsupporting
confidence: 61%
“…In other conditions where cfDNA levels were increased, as observed after physical exercise, DNase1 activity was also elevated [32,42]. A study by Skiljevic et al found that a relapse in SLE patients is characterised by an increase of DNase1 activity but without reaching the levels of healthy individuals [40]. Therefore, we proposed a mechanism of counter regulation where enzyme activity rises in response to the rise of substrate which is, in our study, reflected by higher levels of cfDNA in blood plasma.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Denny et al described a distinct subset of SLE neutrophils, so-called low-density granulocytes, with increased NET releasing capabilities [23]. It has also been reported that SLE patients display a reduced NET clearance capacity due to a decreased DNase I activity and/or NET-bound C1q/ autoantibodies preventing the accessibility to the NETs of DNase I [24,25]. Both increased NETosis and reduced degradation/removal of NETs may lead to an enduring exposure of NET antigens to the immune system, thereby evoking or amplifying an anti-nuclear autoimmune response.…”
Section: Discussionmentioning
confidence: 99%
“…Defects in expression and activity of CRP and SAP also contribute to defective clearance of necrotic cells (66, 68, 76). Some lupus patients have defective serum DNase I activity (157, 158) and they tend to have higher disease activity, and higher autoantibody levels when compared to SLE patients with normal enzyme activity (158). In mice, DNase I deficiency results in a lupus-like syndrome with glomerular immune complex deposition and glomerulonephritis (157).…”
Section: Defective Clearance Of Necrotic Cells In Lnmentioning
confidence: 99%